2021
DOI: 10.1177/2152656720988565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In-Office Cryoablation of Posterior Nasal Nerves for the Treatment of Rhinitis

Abstract: Background Chronic rhinitis is a common condition generally treated with medical therapies. However, 10–22% of patients are refractory to medical therapies. A cryotherapy handheld device targeting the postganglionic nerve fibers of the posterior nasal nerve (PNN) now serves as an additional option for therapy. This study evaluates the efficacy of the cryosurgical ablation device of the PNN in the clinic setting. Methods This was a prospective single-arm trial of 24 adult patients at seven locations within a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…The results of this study validate the use of cryoablation of the posterior nasal nerve as an effective treatment for chronic rhinitis. In comparison with previous studies on cryoablation of the posterior nasal nerve, our baseline rTNSS score of 8.1 was higher than those previously described by Hwang et al 14 (6.2), Chang et al 15 (6.1), and Yen et al 16 (7.0), and similar to that described by Gerka Stuyt et al 18 (7.8). Despite our participants having more severe baseline symptom scores, our 90‐day active treatment change (−3.7) was similar to changes in those other studies (−3.5, −3.1, −4.0, and −3.9, respectively).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of this study validate the use of cryoablation of the posterior nasal nerve as an effective treatment for chronic rhinitis. In comparison with previous studies on cryoablation of the posterior nasal nerve, our baseline rTNSS score of 8.1 was higher than those previously described by Hwang et al 14 (6.2), Chang et al 15 (6.1), and Yen et al 16 (7.0), and similar to that described by Gerka Stuyt et al 18 (7.8). Despite our participants having more severe baseline symptom scores, our 90‐day active treatment change (−3.7) was similar to changes in those other studies (−3.5, −3.1, −4.0, and −3.9, respectively).…”
Section: Discussionsupporting
confidence: 88%
“… 7 More recently, selective cryoablation of the posterior nasal nerve has shown promise in nonrandomized studies for reducing rhinorrhea and nasal congestion in patients with allergic and nonallergic rhinitis, but the lack of a control arm has limited interpretation of the data from these trials. 14 , 15 , 16 , 17 , 18 The present study was designed to address this limitation by including a randomized, sham‐controlled arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in 1983. Studies utilizing cryoablation, including a randomized, sham‐controlled trial, have shown improvement in symptoms and QOL 275,2404–2409 . Though no study specifically evaluated an AR‐specific cohort, many performed subgroup analysis (which showed similar improvement) or controlled for the presence of AR (which showed that AR did not modify outcomes).…”
Section: Managementmentioning
confidence: 99%